Aisyiyah's Role in Stunting Prevention through Educational Kit in Pandemic Covid 19 In Tamansari Health Center (Puskesmas Tamansari) Working Area of Tasikmalaya City - Neni Nuraeni; Gugun Gundara; Azizah Azizah; Eka Eka; Mukhsin Mukhsin; Dede Nano (ABDIMAS: Jurnal Pengabdian Masyarakat, 2022)
The numbers of stunting issue in Indonesia is currently still high although various program efforts and activities carried out by the government including in Puskesmas Tamansari Working Area are vociferous to prevent stunting and reduce stunting rates. In line with the program Aisyiyah branch of Muhammadiyah University of Tasikmalaya in efforts to prevent stunting to improve the quality and competitive of human resources including avoiding stunting by encouraging the government to give priority to stunting rate reduction programs, implement policies in earnest by moving all bureaucratic devices and synergizing with community groups. The purpose of this activity is to provide education to the community, especially cadres and adolescents in the prevention of stunting during the COVID 19 pandemic. The activities are carried out by providing educational kits containing materials and videos about household PHBS, stunting prevention in pregnant women and adolescents. This educational kit is given to cadres as part of the community in providing the first information of stunting prevention and health education directly to cadres and adolescents. The activities held on November 23rd, 2021 to all cadres out of Setiawargi and Posyandu Remaja Setiamulya. The implementation of the activities is carried out by lecturers and students and assisted by the person in charge of nutrition program and UKS PKM Tamansari Kota Tasikmalaya